1999
DOI: 10.1089/107999099314117
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids Synergize with Interleukin-2 to Augment IFN-gamma and Interleukin-12 Production by Human Peripheral Blood Mononuclear Cells

Abstract: We have demonstrated previously that cells from both the skin and peripheral blood from patients with cutaneous T cell lymphoma (CTCL) have elevated levels of protein and mRNA for Th2 cytokines, interleukin-4 (IL-4) and IL-5, and depressed levels of Thl cytokines, IL-2 and interferon-gamma (IFN-gamma). Furthermore, IL-12 in vitro can restore IFN-gamma production by these patients' cells to near normal levels. Because retinoids exert therapeutic activity in CTCL and are potent modulators of growth and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Furthermore, a similar, selective defect in IL-2-induced IFN-␥ production was demonstrated for patients with IL-12R␤1 mutations (18). This phenomenon probably reflects the important role that IL-12 costimulation plays in IFN-␥ induction by IL-2 (27,28) and suggests that endogenous IL-12 contributes significantly to the ability of IL-2 to induce IFN-␥ production in vitro using activated PBMC. This is further supported by our observation that a neutralizing IL-12 Ab impaired IL-2-induced IFN-␥ production in assays using activated PBMC from controls.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, a similar, selective defect in IL-2-induced IFN-␥ production was demonstrated for patients with IL-12R␤1 mutations (18). This phenomenon probably reflects the important role that IL-12 costimulation plays in IFN-␥ induction by IL-2 (27,28) and suggests that endogenous IL-12 contributes significantly to the ability of IL-2 to induce IFN-␥ production in vitro using activated PBMC. This is further supported by our observation that a neutralizing IL-12 Ab impaired IL-2-induced IFN-␥ production in assays using activated PBMC from controls.…”
Section: Discussionsupporting
confidence: 56%
“…Using a number of different RAR-specific retinoids, including all-trans-retinoic acid and 13-cis-retinoic acid, Fox et al, demonstrated that these compounds exhibited the capacity to induce IL-12-dependent IFN-γ production (75). Moreover, synergistic production of IFN-γ occurred when low concentrations of IL-2 were added to the RAR-specific retinoids.…”
Section: Figurementioning
confidence: 99%
“…Thus, the overall efficacy of a regimen is unlikely to reflect only the effect of the timing of the first dose, and the superior efficacy of pentasaccharide over enoxaparin is likely to be due to its selective inhibition of activated factor X, its rapid onset of action, and its long half-life, which results in a complete, 24-hour antithrombotic effect. 4,5 The reports of neuraxial hematomas referred to by Dr. Landow led to strengthened precautions for the use of anticoagulation in conjunction with epidural or spinal anesthesia. Our patients underwent randomization postoperatively and only after the removal of any epidural catheter.…”
Section: The Authors Replymentioning
confidence: 99%
“…Yet it is clear from other data that aggressive lipid management leads to clear benefit within six months of initiating therapy. 4,5 As compared with coronary angioplasty, aggressive lipid lowering with 80 mg of atorvastatin (bringing the ratio of total cholesterol to high-density lipoprotein cholesterol down to 2.8) decreased the rate of ischemic events by 36 percent over a period of 18 months. 4 Since no trial has compared stateof-the-art medical management (especially aggressive lipid lowering) with surgery, it is difficult to conclude that coronary revascularization is underutilized, especially for patients with chronic cardiac symptoms.…”
Section: The Authors Replymentioning
confidence: 99%
See 1 more Smart Citation